Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2478/v10007-011-0037-z
|View full text |Cite
|
Sign up to set email alerts
|

Crystal modifications and dissolution rate of piroxicam

Abstract: Crystal modifications and dissolution rate of piroxicam Piroxicam is a nonsteroidal anti-inflammatory drug with low aqueous solubility which exhibits polymorphism. The present study was carried out to develop polymorphs of piroxicam with enhanced solubility and dissolution rate by the crystal modification technique using different solvent mixtures prepared with PEG 4000 and PVP K30. Physicochemical characteristics of the modified crystal forms of piroxicam were investigated by X-ray powder diffractomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…It was concluded in their study that the needle forms showed improved dissolution but not the solubility. Similarly, the cube‐shaped crystals from the slow evaporation method which included addition of polymer such as polyvinylpyrrolidone K30 and polyethylene glycol 4000 showed improved solubility but not solubility . In our study, by the inclusion of the 15% w/v poloxamer in the formulation, not only the dissolution but also the solubility of the drug was increased as shown in the permeation profile.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…It was concluded in their study that the needle forms showed improved dissolution but not the solubility. Similarly, the cube‐shaped crystals from the slow evaporation method which included addition of polymer such as polyvinylpyrrolidone K30 and polyethylene glycol 4000 showed improved solubility but not solubility . In our study, by the inclusion of the 15% w/v poloxamer in the formulation, not only the dissolution but also the solubility of the drug was increased as shown in the permeation profile.…”
Section: Discussionsupporting
confidence: 48%
“…Similarly, the cube-shaped crystals from the slow evaporation method which included addition of polymer such as polyvinylpyrrolidone K30 and polyethylene glycol 4000 showed improved solubility but not solubility. [27] In our study, by the inclusion of the 15% w/v poloxamer in the formulation, not only the dissolution but also the solubility of the drug was increased as shown in the permeation profile. As reported by Lyn et al, recrystallized piroxicam using slow crystallization method produced cube-shaped crystals which displayed better dissolution profile than the untreated piroxicam.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The principal effective component of curcuma is curcumin [9]. Crystal curcumin is a light yellow powder, soluble in ethanol, acetone, ethylene glycol and alkaline solution, insoluble in water, and slightly soluble in vegetable oil [10]. Curcumin exhibits antitumor, antiviral, anti-inflammatory, anti-oxidant, antiatherosclerotic, anti-fibrotic, hypo-lipidomic, and liver-and kidney-protecting features [11,12].…”
Section: Introductionmentioning
confidence: 99%